2007
DOI: 10.1021/bc700227z
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Nanoparticle−Peptide Conjugate Effectively Targets Intercellular Cell-Adhesion Molecule-1

Abstract: Targeted delivery of therapeutics possesses the potential to localize therapeutic agents to a specific tissue as a mechanism to enhance treatment efficacy and abrogate side effects. Antibodies have been used clinically as therapeutic agents and are currently being explored for targeting drug-loaded nanoparticles. Peptides such as RGD peptides are also being developed as an inexpensive and stable alternative to antibodies. In this study, cyclo(1,12)PenITDGEATDSGC (cLABL) peptide was used to target nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 41 publications
5
161
0
Order By: Relevance
“…Poly(DL-lactide-co-glycolide) (PLGA) is a copolymer that allows controlled release of drug over time or in response to a biological cue. 15 PLGA has many advantages over other polymers used in drug and gene delivery including biodegradability, biocompatibility, and approval for human use granted by the US Food and Drug Administration (FDA). 16 We have successfully delivered plasmid DNA, [17][18][19] drugs, 13,19,20 and peptides 21 by using PLGA-NPs in our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(DL-lactide-co-glycolide) (PLGA) is a copolymer that allows controlled release of drug over time or in response to a biological cue. 15 PLGA has many advantages over other polymers used in drug and gene delivery including biodegradability, biocompatibility, and approval for human use granted by the US Food and Drug Administration (FDA). 16 We have successfully delivered plasmid DNA, [17][18][19] drugs, 13,19,20 and peptides 21 by using PLGA-NPs in our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these peptides have also been developed and tested in the context of blocking ICAM-1-mediated adhesion during inflammation and cancer metastasis and have been shown to bind to human ICAM-1 but have not been tested in other species. Arguably, the most interesting example of such a peptide from the perspective of targeting drug delivery systems to ICAM-1 is cLABL, which has been shown to provide efficient binding to human epithelial and endothelial cells (Zhang et al, 2008;Chittasupho et al, 2009). The species cross-reactivity of this peptide, en- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the feasibility of passive targeting, neovascularization is a critical component of rheumatoid arthritis pathogenesis (Szekanecz & Koch, 2008). Adhesion molecules, including intercellular cell-adhesion molecule-1 (ICAM-1) and E-selectin, are upregulated within the newly formed vasculature and; therefore, the endothelium serves as another possibility for active targeting (Banquy et al, 2008;Zhang et al, 2008). Preliminary studies demonstrated that a large number of PLGA-PEG nanoparticles surface modified with a peptide specific for ICAM-1 were endocytosed by vascular endothelial cells as compared to unmodified particles (Zhang et al, 2008).…”
Section: Active Targeting Strategiesmentioning
confidence: 99%
“…Adhesion molecules, including intercellular cell-adhesion molecule-1 (ICAM-1) and E-selectin, are upregulated within the newly formed vasculature and; therefore, the endothelium serves as another possibility for active targeting (Banquy et al, 2008;Zhang et al, 2008). Preliminary studies demonstrated that a large number of PLGA-PEG nanoparticles surface modified with a peptide specific for ICAM-1 were endocytosed by vascular endothelial cells as compared to unmodified particles (Zhang et al, 2008). A similar phenomenon was observed for polyester-based polymeric nanoparticles labeled with ligand specific for E-selectin (Banquy et al, 2008).…”
Section: Active Targeting Strategiesmentioning
confidence: 99%